THE TEAM AND MANAGEMENT FORMATION FEATURES IN A PROJECT - RATUSHNYAK, Olga (Herald of Khmelnytskyi National University. Economic sciences, 2025)
The paper examines various scientific approaches to the concept of a project team and forms a generalised concept on their basis. It is emphasised that when creating a project team, it is necessary to consider the features of the organisational structure used in a specific project. The functional, matrix, project and flexible organisational structures, their advantages and disadvantages, and their impact on the project team's work are considered. A general information model of project team formation is presented, which includes the collection, processing and analysis of input information for forming a project team, the use of tools and methods and the formation of final details, which provides for the generalisation, documentation of decisions regarding the composition, responsibility, work plan and interaction mechanism.The main stages that must be completed when forming and managing a team are highlighted, namely formation, churning, standardisation, functioning, and completion, and their characteristics are given. The main stages of project team formation include selecting participants, defining roles, creating effective interaction, and monitoring performance. The main elements that influence the team formation and management process are considered.The main principles that must be followed when forming and managing a project team are presented: clear definition of roles and goals, competence and professionalism, complementarity, leadership and responsibility, communication and cooperation, flexibility and adaptability, motivation and involvement, trust and mutual respect, clear resource management, and continuous development.The competencies that a manager should consider when selecting a project team are considered. Based on these competencies, a mathematical model for selecting a project participant is proposed, which includes maximum technical, managerial, communication, leadership, flexible, adaptive, ethical, and social competencies and minimal costs.
Keywords: project; project team; project manager; competencies; management